Factors associated with absenteeism from medical appointments, Hospital Nacional Daniel Alcides Carrión - Soto Asencios, Ninfa Eulalia (2024)
Objective: To determine the factors associated with the absenteeism from medical appointments among patients at a national hospital in Peru. Materials and methods: An observational, retrospective and analytical case-control study among patients who either missed or attended their scheduled medical appointments. The population of absentees was 2,963, while that of attendees was 12,125 patients. The sample consisted of 126 scheduled individuals in the case group and 253 in the control group, selected by systematic sampling, considering selection criteria. From the appointment scheduling records and the medical consultation database, personal factors such as place of residence, condition in the facility, condition in the service, financing and sex as well as institutional factors such as the deferral of appointments were collected using a data collection form. The associated factors were analyzed using binary logistic regression. Results: The absenteeism rate was 19.64 %. A total of 81.75 % of absent patients and 65.22 % of those in the control group receive medical care through the Sistema Integral de Salud (SIS, Comprehensive Health Insurance) scheme. Furthermore, 68.25 % of the absentees booked their medical appointment seven or more days in advance, compared to 51.38 % of the control group. The factors associated with absenteeism were financing (p = 0.002; OR = 2.385; 95 % CI [1.365-4.168]) and the deferral of the appointment (p = 0.005; OR = 1.965; 95 % CI [1.225-3.152]). Regarding the likelihood of being absent, that of SIS beneficiaries was 2.385, while that of users who scheduled an appointment seven or more days in advanced was 1.965. Conclusions: Being a SIS beneficiary patient and the granting of an appointment deferred by more than seven days increases the probability of absenteeism from scheduled medical appointments. A processes review is suggested as a part of the continuous improvement.